Structural behaviour of mortar-less interlocking masonry system under eccentric compressive loads - Waleed A., Thanoon; M. S., Jaafar; J., Noorzaei; M. Razali A., Kadir; S., Fares (MULTI SCIENCE PUBL CO LTD, 5 WATES WAY, BRENTWOOD CM15 9TB, ESSEX, ENGLAND, 2007)
Interlocking masonry wall as a structural load-bearing element is still unexplored simply because its basic behaviour and complete response to failure is not known. In addition, there is no design code available to provide necessary guidance for a safe design of interlocking walls. This paper provides an attempt to ascertain the structural response of interlocking masonry walls compared to conventional bonded walls. Individual block units, prisms and full-scale wall specimens were tested under the action of concentric and eccentric compressive loads. The effect of different patterns of reinforced concrete stiffeners has also been investigated. The test results were discussed in terms of wall efficiency, strength capacity, deflection, strain distribution, cracking patterns and failure modes. The results indicate a promising future use of the interlocking masonry system in construction.